2011
DOI: 10.1371/journal.pone.0017312
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase Levels Are Elevated in the Urine and Plasma of Type 2 Diabetes Patients and Associate with Blood Glucose Levels

Abstract: Heparanase is an endoglycosidase that specifically cleaves heparan sulfate side chains of heparan sulfate proteoglycans. Utilizing an ELISA method capable of detection and quantification of heparanase, we examined heparanase levels in the plasma and urine of a cohort of 29 patients diagnosed with type 2 diabetes mellitus (T2DM), 14 T2DM patients who underwent kidney transplantation, and 47 healthy volunteers. We provide evidence that heparanase levels in the urine of T2DM patients are markedly elevated compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 47 publications
4
80
1
Order By: Relevance
“…25 We have also reported that HG can stimulate the secretion of both latent and active forms of heparanase from EC. 26 As EC behave differently based on their vessel type and environment, 27 in this study, we compared the effects of HG on releasing Hep …”
Section: Macrovascular and Microvascular Ec Secretion And Reuptake Ofmentioning
confidence: 82%
“…25 We have also reported that HG can stimulate the secretion of both latent and active forms of heparanase from EC. 26 As EC behave differently based on their vessel type and environment, 27 in this study, we compared the effects of HG on releasing Hep …”
Section: Macrovascular and Microvascular Ec Secretion And Reuptake Ofmentioning
confidence: 82%
“…Interestingly, insulin is known to stimulate heparanase secretion from cells (44), raising the possibility that insulin plays a dual role in activating ERK signaling via insulin receptor regulation and by enhancing secretion of heparanase, which further drives insulin receptor signaling and ERK activation. These findings underscore the potential of heparanase inhibitors and insulin receptor pathway inhibitors as anti-cancer drugs and the possibility that they could be used to reverse the aggressive phenotype of some myeloma tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, it becomes increasingly clear that immunocytes are not the sole source of the enzyme in inflammation. Up-regulation of heparanase, locally expressed (i.e., by epithelial cells, vascular endothelium) at the site of inflammation, was demonstrated in the mouse models of delayed type hypersensitivity [57], chronic colitis [29], psoriasis (our unpublished results), as well as in several auto-immune and auto-inflammatory human disorders, including rheumatoid arthritis [88], type 2 diabetes [89], ulcerative colitis, and Crohn's disease [29,30].…”
Section: Heparanase In Inflammationmentioning
confidence: 91%